Self-Harm Inventory (SHI) Versi Indonesia Sebagai Instrumen Deteksi Dini Perilaku Self-Harm - Andrian Fajar Kusumadewi; Bambang Hastha Yoga; Sumarni Sumarni; Silas Henry Ismanto (Jurnal Psikiatri Surabaya, 2020)
Background: Self-harming behavior (SHB) is an iceberg phenomenon commonly occurred in both normal population and patients with mental illness. This behavior showed an increase in trend and may develop into suicidal behavior if not treated properly. Therefore an effort in screening and prevention of self-harm is necessary to prevent early deaths caused by suicide. Currently Indonesian version of self-harm screening instrument has not been developed yet.Purpose: Conducting validity and reliability test of Indonesian version of self-harm questionnaire.Method: This research was a descriptive analytic study with cross-sectional design. We recruited 110 psychiatric outpatients from Bantul Hospital Yogyakarta (n=110). SHB was measured using Indonesian version of Self Harm Inventory (SHI). Internal validation was tested using Aiken's Validity Index (AVI) and Pearson Product Moment Correlation (PPMC). Reliability was tested using Cronbach Alpha (CA). Statistical significance was defined as p<0,05.Result: The respondents consisted of 57 men (51.8%) and 53 women (48.2%). Twenty four respondents had done more than 5 items of SHB. AVI value ranged from 0.83 to 0.97 which considered good. PPMC obtained 21 valid items with correlation coefficient >0.25 (p <0.05). Item number 22 was excluded because coefficient value was <0.25. Rresult of Keizer Meyers Oklin was 0,686 and Barlett Test of Spherecity 0,000 (p <0,05). CA was 0.831 which means very good.Conclusion: Indonesian version of Self-Harm Inventory is a valid and reliable screening tool against self-harm behavior in clinical setting.